2020
DOI: 10.3390/microorganisms8121931
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Decay Behavior of Two White-Rot Fungi in Relation to Wood Type and Exposure Conditions

Abstract: Fungal wood decay strategies are influenced by several factors, such as wood species, moisture content, and temperature. This study aims to evaluate wood degradation characteristics of spruce, beech, and oak after exposure to the white-rot fungi Pleurotusostreatus and Trametesversicolor. Both fungi caused high mass losses in beech wood, while spruce and oak wood were more resistant to decay. The moisture content values of the decayed wood correlated with the mass losses for all three wood species and incubatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 45 publications
8
30
1
3
Order By: Relevance
“…All three species caused white rot, which would be expected to utilize lignin. The lignocellulosic-degradative capacities for Pleurotus species have been explored on oak [ 42 , 43 , 44 ] and beech wood [ 45 , 46 , 47 , 48 ], and it has been suggested that these fungi modify their decay modes (i.e., simultaneous to selective rot), depending on the environmental conditions [ 45 , 49 , 50 , 51 ]. The blocks exposed to T. versicolor , F. fomentarius , and P. chyrsosporium also contained lower amounts of lignin than the controls.…”
Section: Resultsmentioning
confidence: 99%
“…All three species caused white rot, which would be expected to utilize lignin. The lignocellulosic-degradative capacities for Pleurotus species have been explored on oak [ 42 , 43 , 44 ] and beech wood [ 45 , 46 , 47 , 48 ], and it has been suggested that these fungi modify their decay modes (i.e., simultaneous to selective rot), depending on the environmental conditions [ 45 , 49 , 50 , 51 ]. The blocks exposed to T. versicolor , F. fomentarius , and P. chyrsosporium also contained lower amounts of lignin than the controls.…”
Section: Resultsmentioning
confidence: 99%
“…Mucidula mucida (of the order Agaricales, as Oudemansiella mucida) and Meripilus giganteus (of the order Polyporales) caused either soft or white rot, depending on decay stage and substrate (host species, and type of wood and plant cell composition) [98,99]. Recently, Pleurotus ostreatus, a species typically reported to cause white rot, was reported to produce soft-rot like symptoms [100].…”
Section: Discussionmentioning
confidence: 99%
“…TV belongs to a group of simultaneous degraders, meaning that it degrades all cell-wall components simultaneously (cellulose, hemicelluloses and lignin). Brown rot fungi rapidly and extensively depolymerise cellulose and hemicelluloses, leaving behind lignin, which is only partially modified and the cell wall is transformed into a porous structure [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%